Students’ Perception toward Supervisors’ Written Feedback in Writing Thesis Proposal - Ivan Achmad N; Sentia Islamiati (Teaching English and Language Learning English Journal, 2022)
This research aimed to find out what are students’ perception toward supervisor’s written feedback in writing thesis proposal. The researcher used descriptive qualitative method. The subjects of this research were 20 students of eighth semester students who are preparing thesis proposal in 2021 Academic Year in English Education Study Program at Muhammadiyah University of Bengkulu. The researcher used observation checklist adapted from Wolflok's theory. The researcher used photos sent via WhatsApp media by 8th semester students as the subject of this study. The researcher used descriptive method to analyze the data. The result of this study showed that the perception of students in the feedback provided by the supervisor really helped them in correcting errors in a thesis proposal writing, especially when the supervisor provided constructive motivation in the form of suggestions or solutions. There were 4 types of feedback given by the supervisor when conducting guidance namely comments, circles and underlines, mark and correct and other signs. Keywords: Supervisor Feedback, Thesis Proposal Writing, Perception.